Emotion and Figurative Language in Taylor Swift’s Selected Songs - Dewi, Ni Nengah Wulan Anggita; Afrianto, Afrianto (Universitas Muhammadiyah Barru, 2026)
This research explores the connection between symbolic language and how emotions are portrayed in Taylor Swift’s selected songs: The Prophecy and The Smallest Man Who Ever Lived. Based on a descriptive qualitative approach, this investigation aims to explore how rhetorical devices, including metaphors, personification, irony, and hyperbole, serve as methods for conveying complex emotional states. The results suggest that within